Effect of Diode Laser and Fluoride Varnish on Microhardness of enamel: An In Vitro Study: Diode laser and fluoride varnish effect on enamel - Najjaran, Hanieh; Safari, Fatemeh; Valizadeh, Sara; Keshvad, Mohammad Ali; Kharazifard, Mohammad Javad; Chiniforush, Nasim; Arab, Sepideh (Journal of Lasers in Medical Sciences, 2024)
Introduction: White spots are a common complication of orthodontic treatment. Several prevention methods such as fluoride therapy and laser irradiation have been proposed, but there is still no conclusive evidence. Therefore, this study aimed to evaluate the combined application of diode laser and fluoride varnish in preventing white spots. Methods: Thirty-nine sound human premolars were extracted for orthodontic purposes and randomly divided into three groups of thirteen teeth each (C: Control, FV: fluoride varnish (5% sodium fluoride), and FV+L: fluoride varnish+980 nm diode laser (2 W)). The freshly extracted teeth were disinfected in a 0.5% chloramine T solution and stored in saline at room temperature. Each tooth was coated with nail polish, leaving a 2×3 mm2 window on the midbuccal. Surface treatments were applied, and primary Vickers microhardness was evaluated in the gingival sections. Then, the samples were immersed in alternating demineralizing (6 hours/day) and remineralizing (18 hours/day) solutions and incubated at 37 °C for 9 days to produce artificial caries. Afterward, the samples were immersed in a remineralizing solution for one day. Finally, secondary microhardness was measured. The data were analyzed using one-way ANOVA. Results: The primary microhardness was higher in groups C and FV than in group FV+L. The lowest secondary microhardness was recorded in group C, and there was no significant difference between the other two groups. The change in microhardness was greater in group C, while no difference was observed between the FV and FV+L groups. Conclusion: Within the limitations of this study, the combined application of laser irradiation and fluoride varnish may not improve white spot lesion (WSL) prevention compared to the use of fluoride varnish alone.